EXPRESSION OF STROMAL CELL DERIVED FACTOR IN THE SPLEEN DURING RODENT MALARIA - Macedo, B; Hermida, FPM; Fernandes, ER; Andrade-Jr, HF (Revista do Instituto Adolfo Lutz, 2009)
n malaria, the clearance of parasitized red blood cells (pRBC) is dependent of spleen. During this infection, the spleen receives a large amount of deformed erythrocytes, which cause a congestion and interruption of spleen circulation. To promote cell migration and, consequently, increase its structure, the spleen starts to release many signals, as CXCL12/SDF-1alpha from stromall cells. We studied the expression of CXCL12/SDF-1alpha to define its importance in spleen amplification during rodent malaria. Chemokine immunohistochemistry was performed in spleen tissue of C57BL/6 mice infected with 106 pRBC of Plasmodium chabaudi CR (non-lethal), P. chabaudi AJ (lethal) and P. berguei ANKA (lethal). In non-lethal strain, we observed no change in morphology of the spleen during the expansion, but it was not found in lethal strains. The CXCL12/SDF-1alpha immunohistochemistry showed an increase of expression of this chemokine in red pulp during malaria infection in all models. In P. chabaudi infection, the AJ strain caused a lower chemokine expression than CR strain at the 6th day p.i., while in P. berghei infection, the chemokine expression was higher than others strains, but with an irregular frequency. Our result showed a significant increase of expression of CXCL12/SDF 1-alpha during the infection when compared to the control group and it may indicate the CXCL12 as an important chemokine in parasitemia control of rodent malaria.